Diseño y construcción de un prototipo de mini bomba neumática para la extracción de agua, destinada al laboratorio de mecánica de fluidos de la carrera de Ingeniería Electromecánica de la Universidad Nacional de Loja. - Yaguana Apolo, Álvaro Alonso (2019)
In the present research work, a prototype of a pneumatic mini pump was made for the Energy and Fluids Laboratory of the Electromechanical Engineering of the National University of Loja (UNL), where students can perform the study on its functionality, analyze its characteristics and link it with laboratory practice. The mini pumping system is composed of a compressor where the compressed air is the working fluid to operate a pneumatic pump submerged in a water reservoir, this involves a chamber with two retention valves, one at the top for the discharge of water and the other at the bottom for water loading. To evacuate this fluid through a hydraulic system, float level sensors activate and deactivate the EVA and EVB solenoid valves for the entry and exit of compressed air, which is operated by a semi-automatic control system. Through the methodology used, information from the Internet was compiled such as: institutional bibliographic repository of the UNL, thesis articles, books, reports and videos, in addition to consultations with teachers of the Electromechanical Engineering degree. Once the corresponding information was systematized and considering the proposed data of the pumping system, the design, selection and construction of hydraulic and pneumatic components was carried out according to the design parameters (pumping flow and gauge height). The pumped flow was 5 L / min and the discharge height 12m. The parts that make up the pneumatic pump such as the chamber and the upper and lower cover were constructed of galvanized iron (HG), the hydraulic accessories that this system entails are made of pvc , except the retention valves TR1 and TR2 type sphere that are material of stainless steel (see annex 5 ) . Regarding the pneumatic component, the compressor was selected considering the number of cycles pumped and the number of starts of an engine. The capacity of the tank was 24 L. The accessories are made of pvc, except the EVA and EVB solenoid valves that are made of bronze ( see annex 14 ) . The time of each discharge cycle was 7.8 sec, while the average recovery time is 5.5 sec. In annexes are presented tables, graphs, screenshots, plans and guides so that students can perform the practices correctly. Finally, in the experimental phase the operation of the prototype was validated, achieving expected results. The total efficiency considering all the energies that interact with the system (electric, pneumatic, hydraulic) was 3.2%. Keywords: Fluid machines, Mechanical design, Semiautomatic control, Pneumatic pump, Hydraulics.